(untitled) (Research, Society and Development, 2022)
Introduction: The fisherman is a professional who performs their function under precarious conditions, with a high workload. According to studies, excessive force is considered one of the main determining biomechanical factors of work-related musculoskeletal disorders, where low back pain is the most common in fishing. Objective: To compare the level of pain with the functionality of artisanal fishermen with chronic low back pain in the city of Santarém-PA, associated with the Z-20 Fishermen’s Colony (CP Z-20). Methods: This research is characterized as: descriptive, transversal and quantitative. All participants were randomly selected through verbal invitation made during their monthly meeting that takes place at the headquarters of each base nucleus. The Visual Analog Scale of Pain (VAS) was applied to subjectively represent the intensity of low back pain, and the Quebec Lumbar Disability Questionnaire (QBPQ) to measure the functional disability caused by low back pain. Results: The sample consisted of 32 fishermen (n=32). With a VAS distribution score of 37% for moderate pain and 63% for severe pain. This shows high levels of pain perceived by this population. As well as high values in the QBPQ score, indicating a direct and proportional relationship with the highest level of pain and the highest degree of disability linked to low back pain. Conclusion: High levels of low back pain are related to greater functional disability in artisanal fishermen.